2001
DOI: 10.1046/j.1365-2265.2001.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic ACTH syndrome caused by pulmonary carcinoid tumourlets

Abstract: The differential diagnosis of Cushing's syndrome is a major challenge to clinical endocrinologists, especially those infrequent cases referred to as occult ectopic ACTH syndromes. Although bronchial carcinoids are well known to be a cause of Cushing's syndrome due to ectopic ACTH secretion, very few cases of carcinoid tumourlets causing an ACTH ectopic syndrome have been reported, and their origin remains controversial. For some authors, tumourlets and typical carcinoids represent distinct pathological entitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The main symptoms are closely related to the accompanying lung diseases. When hyperplastic PNECs cause tracheal obstruction, stenosis and in ammatory reactions, they can manifest as cough, expectoration, hemoptysis, chest tightness, shortness of breath or progressive dyspnea, and some patients have carcinoid syndromes, such as facial ushing, skin pigmentation, muscle weakness, and diarrhea [7]. Pulmonary carcinoid tumorlets are usually multiple pulmonary nodules that can occur in a single lobe, in multiple lobes, or even in both lungs, and the number ranges from several to dozens [8].…”
Section: Discussionmentioning
confidence: 99%
“…The main symptoms are closely related to the accompanying lung diseases. When hyperplastic PNECs cause tracheal obstruction, stenosis and in ammatory reactions, they can manifest as cough, expectoration, hemoptysis, chest tightness, shortness of breath or progressive dyspnea, and some patients have carcinoid syndromes, such as facial ushing, skin pigmentation, muscle weakness, and diarrhea [7]. Pulmonary carcinoid tumorlets are usually multiple pulmonary nodules that can occur in a single lobe, in multiple lobes, or even in both lungs, and the number ranges from several to dozens [8].…”
Section: Discussionmentioning
confidence: 99%
“…1 Carcinoid tumors can also manifest as tumorlets, but their relationship has not been firmly established. Some authors have claimed that they are a different stage of the same neuroendocrine proliferation, 2 and that tumorlets are simply the intramucosal spread of neoplastic neuroendocrine cells from carcinoids. In this instance, genetic analysis could resolve the pathogenetic relationship between tumorlets and carcinoids.…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological diagnosis was multiple peripheral cartinoid tumors and tumorlets of a carinoid type showing positive immunostaining for ACTH. Povedano et al [13] reported a patient with an aggressive case of Cushing's syndrome that required a bilateral adrenalectomy, diagnosed 22 years before a 3-cm lung nodule became apparent in a chest X-ray. The biopsy after lung surgery revealed a typical peripheral bronchial carcinoid tumor surrounded by tumorlets.…”
Section: Discussionmentioning
confidence: 99%